2014
DOI: 10.1111/1346-8138.12613
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection in Bowen disease: Negative p53 expression, not p16INK4a overexpression, is correlated with human papillomavirus‐associated Bowen disease

Abstract: Genital Bowen disease (BD) has been linked to the high-risk types of human papillomavirus (HPV) infection. Recently, it has been recognized that HPV also can be associated with extragenital BD. HPV oncoproteins E6 and E7 interfere with the function of p53 and pRb, respectively, leading carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…This role was clearly identified in cervical, anogenital, and some oropharyngeal carcinomas. However, the role of mHPV in NMSC carcinogenesis remains unclear …”
Section: Introductionmentioning
confidence: 99%
“…This role was clearly identified in cervical, anogenital, and some oropharyngeal carcinomas. However, the role of mHPV in NMSC carcinogenesis remains unclear …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of p16 immunostaining in premalignant and malignant keratinocytic lesions showed discrepant results . Comparison between these different studies is difficult, because different scoring methods were used.…”
Section: Discussionmentioning
confidence: 96%
“…There is evidence that in OTR HPV plays a role in development of keratinocyte neoplasia. However, no significant association between p16 protein expression and the presence of HPV has been found . The mechanism of p16 expression in keratinocytic neoplasia is not completely understood.…”
mentioning
confidence: 99%
“… References : Daley et al, Gimeno et al, Patterson et al, Ulbright et al, Brentjens et al, Murao et al …”
Section: Discussionmentioning
confidence: 99%